Evaluating Tafsir Maqāṣidī As A Framework For Ecological Crisis Moderation - Cholidi, Muhammad Fiqih; Masuwd, Mowafg Abrahem (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This study aims to re-evaluate the offer of maqāṣidī interpretation in resolving the ecological crisis caused by the anthropocentric paradigm. This study uses a qualitative method to analyze the philosophy and interpretation products of maqāṣidī tafsir through primary sources such as the works of figures who first formulated maqāṣid of the Qur'an as the philosophy of maqāṣidī tafsir and applied it in interpretation products; among them are Rashid Rida and Ṭāhir Ibn 'Āshūr. Based on this evidence, the findings reveal that there is inconsistency in maqāṣidī interpretation in mediating the contestation between theocentric and anthropocentric paradigms, therefore, it can be said that maqāṣidī interpretation is more adapted to the modern context and its needs without a clear frame of reference, rather than referring to God's purpose, although the word maqāṣid is synonymous with God's purpose. As a result, maqāṣidī interpretation does not place meaning in the midst of the contestation of the two paradigms but prefers one of them accordingly fit to the context.